ESTIMATION OF ECONOMIC AND BIOLOGICAL TRAITS OF ALFALFA COLLECTION SAMPLES IN THE ROSTOV REGION - S. А. Ignatiev; А. А. Regidin (Зерновое хозяйство России, 2019)
To stimulate livestock production increase, it is necessary to improve the production of high-quality feed with high protein percentage. The purpose can be achieved by an increase of sown area for perennial leguminous herbs and, in particular, alfalfa. The varietal alfalfa composition is constantly being replenished with new, more productive and adapted varieties for different growing zones. The biological potential of this crop allows now conducting its successful breeding. Annually the FSBSI “Agricultural Research Center “Donskoy” lays the alfalfa collection nurseries including breeding samples from different countries with certain useful traits. According to the study results alfalfa plant height ranged from 75.7 cm (“K-20367”) to 122.5 cm (“G-4”). On average, through the study, the samples formed a low yield of green mass. 19 samples had yields from 1.70 kg/m2 to 2.46 kg/m2 , which is significantly lower than the standard indicator (3.29 kg/m2 ). The samples “K-51698”, “G-1”, “K-50512”, “G-3”, “G-4” produced a significant excess of green mass productivity in comparison with the variety “Rostovskaya 90” (4.13–4.86 kg/m2 ). On average during the years of 2016–2018, foliage amount of the samples varied from 41% to 53%. The samples “K-50512”, “G-1”, “G-3”, “G-4” showed a significant excess of absolutely dry matter (ADM) productivity (from 1.42 kg/m2 to 1.65 kg/m2 ). Among the samples seed productivity varied in the range of 15.2–94.9 g/m2 . Only 3 samples (“K-50511”, “K-51201”, “G-2”) showed a significant excess in the studied traits compared to the standard variety “Rostovskaya 90” (63.3 g/m2 ), their seed productivity was 85.7 g/m2 , 86.8 g/m2 and 94.9 g/m2 , respectively. The protein percentage of absolutely dry matter according to the study ranged from 17.79% to 21.47%. The samples “K-43260” (20.95%), “K-50512” (21.34%), “K-31800” (21.47%) showed the largest indicators. In the current study there have been analyzed correlations between the studied traits.